2020
DOI: 10.3390/foods9040526
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Suppresses the Expression of Oxidative Stress Response and NLRP3 Inflammasome Genes in Aged C57BL/6 Mouse Ovaries

Abstract: Female infertility and subfertility have been increasing in prevalence worldwide. One contributing factor is ovarian function, which is highly age-dependent. Korean red ginseng is widely used as an herbal medicine and has many beneficial properties. We aimed to determine the effect of the Korean red ginseng saponin fraction (KRGSF) on ovarian function in female C57BL/6 mice. Ovaries were isolated from 6- and 12-month-old female mice and treated with KRGSF, and then RNA was extracted and microarray analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A previous study showed that the levels of the products of OS damage (carbonylated and nitrated proteins) and inflammatory markers (TNF-α, IL-1β) were significantly higher in the ovaries of aged mice than in younger mice [ 39 ]. Ovarian RNA transcriptome analysis further revealed that OS-related proteins (Nrf2, SOD2, CAT, GSH-px1) and genes encoding NLRP3 inflammatory vesicles could be used as key biomarkers to differentiate between young and aging mice [ 40 ]. A variety of models of functional ovarian damage were shown to exhibit high levels of inflammatory factors and OS markers [ 41 , 42 ].…”
Section: Pathological Mechanisms Related With Os In Ovarian Agingmentioning
confidence: 99%
“…A previous study showed that the levels of the products of OS damage (carbonylated and nitrated proteins) and inflammatory markers (TNF-α, IL-1β) were significantly higher in the ovaries of aged mice than in younger mice [ 39 ]. Ovarian RNA transcriptome analysis further revealed that OS-related proteins (Nrf2, SOD2, CAT, GSH-px1) and genes encoding NLRP3 inflammatory vesicles could be used as key biomarkers to differentiate between young and aging mice [ 40 ]. A variety of models of functional ovarian damage were shown to exhibit high levels of inflammatory factors and OS markers [ 41 , 42 ].…”
Section: Pathological Mechanisms Related With Os In Ovarian Agingmentioning
confidence: 99%
“…Saponins from P. japonicus treatment have been shown to alleviate high-fat diet (HFD)-induced recognitive impairment and depression-like behaviors in HFD-fed Balb/c mice, which could partly be due to the ability of saponins from P. japonicus to mitigate neuroinflammation through inhibition of NLRP3 inflammasome (NLRP3, caspase-1, ASC, and IL-1β) and upregulation of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors signaling pathway [ 71 ]. Saponin fraction of KRG reveals an anti-inflammatory effect by ameliorating the mRNA expression of genes encoding NLRP3 inflammasome components (Nlrp3, Asc, pro-IL-1β, IL-1β, pro-caspase-1, and caspase-1) in cultured ovaries from aged C57BL/6 mice [ 72 ] ( Table 1 ). Taken together, these findings indicate that saponin fraction may be used as a potential agent for the treatment of infection and inflammation-related neurological diseases.…”
Section: P Ginseng As a Potential Therapeutic For Neurologic...mentioning
confidence: 99%
“…Rb1, Rg1, Rg2, Rg3, Rg5, Rd, Re, Rh1, 25-OCH 3 -PPD, and compound K (CK) in Panax ginseng inhibit NLRP3 inflammasome stimulation, leading to suppressed inflammatory responses and multiple disease conditions, such as obesity, gouty arthritis, atherosclerosis , non-alcoholic fatty liver disease, liver injury, hyperlipidemia, type I diabetes, myocardial hypertrophy and dysfunction, cerebral ischemia and reperfusion injury, colitis, hepatic fibrosis, sepsis, neuronal damage, kidney injury, and cognitive deficits [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] ]. Korean red ginseng (KRG) extract and KRG saponin fraction in Panax ginseng also inhibited inflammatory responses by inhibiting NLRP3 inflammasome activation in macrophages, monocytes, sepsis mice, and aging mice [ 65 , 74 ]. Chikusetsu saponin IVa, a major active triterpenoid saponin in Panax japonicus , inhibited NLRP3 inflammasome activation, hence ameliorating obesity and neuroinflammation in macrophages, adipocytes, primary neurons, and postoperative cognitive dysfunction rats [ 75 , 76 ].…”
Section: Inhibitory Role Of Ginseng In Inflammasome Activationmentioning
confidence: 99%